Antioxidant Activity Test of Barangan Banana Hump’s Ethanol Extract (Musa Paradisiaca (L.)) with DPPH (1,1 Diphenyl-2-Picrylhydrazyl) Method - Nurmazela, Virda; Ridwanto, Ridwanto; Rani, Zulmai (International Journal of Science, Technology & Management, 2022)
This study aims to determine the secondary metabolites contained in Barangan banana weevil (Musa paradisiaca (L.)) and antioxidant activity based on the IC50 value. The stages of this research include processing plant materials, making ethanol extracts, characterization examinations, phytochemical screening, and testing the antioxidant activity of Barangan banana weevil. The ethanol extract of Barangan banana weevil was processed by the maceration method using 96% ethanol, and the antioxidant activity was tested using the DPPH method. The results showed that the ethanol extract of Barangan banana weevil contained chemical compounds such as alkaloids, glycosides, flavonoids, saponins, tannins, and triterpenoids. The determination of the antioxidant activity of Barangan banana weevil obtained an IC50 value of 180.8 µg/mL. This means that the ethanol extract of Barangan banana weevil contains secondary metabolites and has the potential as an antioxidant with a weak category.